Does rehabilitation pose a risk to patients suffering from haemato‐oncological diseases? Results of a monocentric, retrospective analysis in Germany. (6th December 2019) - Kiefer, Thomas; Krahl, Dorothea; Kohlmann, Thomas; Nogai, Axel; Baurmann, Herrad; Schüler, Frank; Krüger, William; de Wit, Maike; Pink, Daniel; Dietz, Marion; Völler, Heinz; Buhlert, Hermann; et al.
Abstract: Objective: Patients suffering from haemato‐oncological diseases tend to have a weakened immune system after the end of their therapy. To avoid infections, patients are advised to limit contact with other people. This poses the question whether a stay at a rehabilitation facility can be recommended. Methods: We report about 134 rehabilitation stays of patients. Premature discontinuation of the rehabilitation stay was selected as the criterion for a serious complication during the rehabilitation, and the underlying reasons were analysed. Results: Compared to the discontinuation rates of patients suffering from solid tumours (2.4%), the percentage of haemato‐oncological patients ending prematurely their rehabilitation stay (8.2%) is significantly increased. This rises to 17.1% for patients who have undergone an allogeneic stem cell transplantation. The analysis of the discontinuation reasons revealed that they were not directly connected to the rehabilitation. Apart from the already known risk factors for premature termination of the rehabilitation stay, we have identified the period (days) between the last therapy and the beginning of the rehabilitation stay as a risk factor. Conclusions: We show for the first time that a rehabilitation stay does not pose additional risks for patients suffering from haemato‐oncological diseases.